Analisis Faktor-faktor yang Memengaruhi Volume Penjualan Herbisida Glifosat Posat di PT Hibrida Jaya Utama, Kota Semarang - Intan, Alfina; Setiadi, Agus; Setiyawan, Hery (Universitas Galuh, 2025)
Glyphosate herbicide was a type of chemical pesticide that was widely used to eradicate weeds in various fields, not only in agriculture. This research was conducted at PT Hibrida Jaya Utama, Semarang, Central Java. The purpose of this study was to identify the factors that affected the sales volume of glyphosate Posat herbicide at PT Hibrida Jaya Utama and analyze the factors that influenced the sales volume of glyphosate Posat herbicide at PT Hibrida Jaya Utama. The method of determining the location was done intentionally. The research method used was the case study method. The primary data used were the results of interviews with resource persons at PT Hibrida Jaya Utama, and the secondary data used were sales data from Posat and prices from Posat and Roundup in 2020-2024. The data analysis method used multiple linear regression analysis. The results of multiple linear regression analysis showed that product prices and competitor prices had a negative effect on the sales volume of Posat glyphosate herbicide. Product price did not significantly affect the sales volume of Posat glyphosate herbicide.